청각세포 사멸화 과정에서의 Connexin 43과 간극결합 세포간 신호전달의 역할 - Kim, Yeon Ju (The Graduate School, Ajou University, 2014)
Cis-diamminedichloroplatinum (cisplatin) is one of effective chemotherapeutic drugs for cancer therapy. Nevertheless, most patients treated with cisplatin are exposed to high risk of ototoxicity such as hearing loss or dizziness. It has been reported that ototoxicity occurs in about 75-100 % of patients treated with cisplatin and shows irreversible, cumulative and bilateral characteristics. However, cisplatin-induced ototoxic mechanisms have not been clearly identified yet even through many studies. Histochemical studies on the distribution of cisplatin have shown that spiral ganglions, lateral wall cells, and organ of Cortis are major targets, where many connexins (Cxs) are expressed. Cxs are a family of membrane proteins and these are expressed abundantly in mammalian inner ears. Cxs oligomerize into a hexameric connexon, also known as a hemichannel, and transport to plasma membranes along microtubules finally forming a gap junction between cells. In the inner ear, gap junctions play a critical role in the generation the endocochlear potential, which is required for normal hearing. The aim of this study was to determine the role of gap junctions and their constituents, hemichannels and Cxs in the cisplatin-induced ototoxic mechanism. As a result, I found that inhibition of gap junctional activity with either Cx43 siRNA transfection or a pharmacological drug, 18α-glycyrrhetinic acid in HEI-OC1 auditory cells caused a marked increase in cell viability with a decrease of apoptosis based on cleaved Poly (ADP-ribose) polymerase (PARP) and cleaved caspase 3 levels. Furthermore, I demonstrated that extracellular signal-regulated kinase (ERK) and protein kinase B (Akt) pathways had a significant role in preventing cell death by inhibition of gap junctions. Next, I found that cisplatin did not affect the opening and closure of Cx43-hemichannels in HEI-OC1 cells and Cx43-transfected Cx-deficient HeLa cells. Accumulation of Cx43 was observed around the nuclei of cisplatin-treated cells, whereas Cx43 was scattered in the punctuated form in the cytoplasms as well as on the membranes in normal cells, suggesting that cisplatin may interrupt the trafficking of Cx43s to cell membranes in HEI-OC1 cells. In addition, I investigated whether Cx43 protein itself affected cell viability in response to cisplatin. I found that the knockdown of Cx43 in HEI-OC1 cells resulted in a significant increase in cell viability following cisplatin treatment independent of gap junctions. This response did not change following inhibition of Cx43 transport to the plasma membrane by Brefeldin A. HeLa cells expressing either full lengthen Cx43 and its N-terminal domain or its carboxyl tail, showed higher sensitivity to cisplatin than mock-treated cells. The mitochondrial Cx43 protein level was significantly increased in HEI-OC1 cells after cisplatin treatment in a time-dependent manner, which coincided with the release of mitochondrial cytochrome C into the cytoplasm. These findings suggest that Cx43 plays important roles on cisplatin-induced ototoxic damage through gap junction-dependent or independent processes in auditory cells. The control of the Cx43-mediated signaling may be a potential target for therapeutic strategies for drug-induced ototoxicity.
학위논문(박사)--아주대학교 일반대학원 :의생명학과,2014. 8
Keywords: Gap junction; Hemichannel; Connexin 43; Cisplatin; Ototoxicity; HEI-OC1